Pengaruh Pendapatan Orang Tua dan Prestasi Belajar Terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi Pada Siswa Kelas XII Akuntansi SMK Negeri 2 Pariaman - Afra Mufida; Z Mawardi Effendi (Jurnal Ecogen, 2019)
This researcher aims to determine the factors that influence the Continuing Study Interest to University Students Vocational High School Number 2 Pariaman. The population in researcher is student on class XII Acounting Vocational High School Number 2 Pariaman Academic Year 2019/2020 amounted 107 students. This researcher used proportional random sampling with 85 students as sample. Data collection technique used questionnaire and processing with SPSS program version 21. The result of researcher are Income of Parent don’t Influential to Interest Continuing Study to University and  Achievement of Study Influential to Interest Continuing Study to Universitas in Student Class XII Acounting Vocational High School Number 2 Pariaman. The coefficient determination is 0,075 or 7,5%. The rest is 92,5% influential by other variabel. Keywords:  income of  parents, achievement of study, interests continuing study to university.